Studi Empiris Komparasi Kinerja Keuangan Perusahaan Minyak dan gas Negara Indonesia dan Malaysia - Susanta, Susanta (Jurnal Ilmu Administrasi dan Bisnis, 2009)
The study intents to answer the financial performance in Indonesia and Malaysia country at oil and gas sector industry Samples were taken from companies listed in capital market in Indonesia and Malaysia. Pooled time series data consists of36 for Indonesia and 54 for Malaysia data included in the sampel for six year pen ads of 2002- 200 7. The parametric statictic methods ofpaired samples t-test with their standard were used to test the hypothesis. The results indicate that oil and gas sector industry in hdonesia has three weak financial performance (current ratio, solvensi, total profitability) and one that wealth for internal profitabily. And the result in Malaysia has wealth for ailfinancial performance. Key ivords: oil and gas sector industry, financial perforniance, pooled time series, Indonesia, MalaysiaÂ